Durability of Critical Infrastructure, Monitoring and Testing Proceedings of the ICDCF 2016 - Kravcov, Alexander; Cherepetskaya, Elena B.; Pospichal, Vaclav (Lecture Notes in Mechanical Engineering,, 2017)
This book presents the proceedings of the International Conference on Durability of Critical Infrastructure. Monitoring and Testing held in Satov, Czech Republic from 6 to 9 December 2016. It discusses the developments in the theoretical and practical aspects in the fields of Safety, Sustainability and Durability of the Critical Infrastructure. The contributions are dealing with monitoring and testing of structural and composite materials with a new methods for their using for protection and prevention of the selected objects.